THE EFFECT OF EMOTIONAL INTELLIGENCE ON MATHEMATICAL CONCEPTS UNDERSTANDING OF JUNIOR HIGH SCHOOL STUDENTS - Anisyak Islami; Aan Putra; Ria Deswita; Nur Rusliah (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2020)
Abstract:This study aims to determine the effect of emotional intelligence on the understanding of the mathematical concepts of Junior High School students. This study is a correlational study conducted at SMPN 18 Kerinci with a population of eight grade students SMPN 18 Kerinci. The sample in this study was 59 students selected using a total sampling technique. Data collection instruments used were questionnaires on emotional intelligence and mathematical concepts test. Hypothesis testing used t-test. The findings showed that emotional intelligence influenced the understanding of the mathematical concepts with a determination coefficient of 27.30%.Abstrak:Penelitian ini bertujuan untuk mengetahui pengaruh kecerdasan emosional terhadap pemahaman konsep matematis siswa Sekolah Menengah Pertama. Penelitian ini merupakan penelitian korelasional dengan analisis regresi yang dilakukan di SMPN 18 Kerinci dengan populasi siswa kelas VIII SMPN 18 Kerinci. Sampel dalam penelitian ini berjumlah 59 siswa yang dipilih menggunakan teknik total sampling. Instrumen pengumpulan data yang digunakan adalah angket kecerdasan emosional dan tes pemahaman konsep matematis. Pengujian hipotesis dilakukan dengan menggunakan uji-t. Hasil penelitian menunjukkan bahwa terdapat pengaruh kecerdasan emosinal terhadap pemahaman konsep matematis dengan koefisien determinasi 27,30%.